PEMBEKALAN STRATEGI PENINGKATAN PENJUALAN PRODUK UMKM DI DESA BABAN KECAMATAN GAPURA KABUPATEN SUMENEP - Wahyuni, Purwati Ratna; Rahman, Sindi Arista; Muchtar, R.P. Much (Universitas Al-Amien Prenduan, 2023)
Service is one of the tridharma that must be carried out by lecturers. This briefing was given to managers of Small and Medium Enterprises (MSMEs) Cracker Pangsit in Baban Village, Gapura District, Sumenep Regency which aims to develop strategies for increasing sales and developing the business so that it continues to grow in the future. . This service activity is carried out using descriptive methods accompanied by information on internal and external factors on competitive advantages in the form of raw materials, legality, machines and tools, work methods / technology, packaging, promotion and marketing. The production activities carried out are relatively simple in terms of marketing. The product is packaged using plastic packaging and does not use a sales logo. The result of this service activity is an increase in sales of Dumpling Cracker products processed by MSMEs in Baban Village, Gapura District, Sumenep Regency